Bilateral Laryngocele Causing Epiglottic Deformity and Upper Airway Obstruction - İrfan Kara; Kerem Kökoğlu; Sedat Çağlı; İmdat Yüce (Turkish Archives of Otorhinolaryngology, 2019)

(untitled)
Laryngocele is the cystic dilatation of laryngeal ventricle. Most cases are asymptomatic and incidentally diagnosed in radiologic examinations. Although the etiology is unclear, obstruction, laryngeal pressure, congenital defects are possible risk factors. Computed tomography is the best method for diagnosis. Endoscopic, external or combined approaches have been described in the surgical treatment. Laryngocele should be kept in mind in patients with acute upper airway obstruction. Such patients may require tracheostomy. Some patients with laryngocele can also have laryngeal cancer, in which case direct laryngoscopy must be performed. This report presents a case with respiratory distress associated with bilateral laryngocele, and his management in the light of the literature.